ANALISIS YURIDIS TERHADAP PEMUTUSAN HUBUNGAN KERJA AKIBAT KEBERATAN DIMUTASI (STUDI PUTUSAN NOMOR 24/PDT.SUS-PHI/2022/PN MKS) - Hasanudin, Yulita Erika; Rahmi, Adelia Hidayatul; Melati, Nanda Sukma; Antonio, Christofher Dylan; Atriani, Dewi (Gorontalo Law Review, 2024)
While it's true that some mutations try to improve workers' wellbeing, others cause Termination of Employment (PHK) as a result of refusal of transfers. Consequently, it is essential that the regulation of employee transfers be carefully considered to ensure compliance with all applicable laws. This study has shown that the legislative provisions pertaining to the termination of employment (PHK) have been met by the action taken by KSP Nasari Makassar against Plaintiff Idiamin Sartian Umar so that it does not harm the party concerned. plaintiff's workers' rights. Then, the transfer carried out by KSP Nasari Makassar was aimed at improving welfare through increasing salaries and promotions for the Plaintiff. However, the Plaintiff refused for personalreasons which violated the Nasari Savings and Loans Cooperative (KSP) Regulations which emphasized that workers must prioritize the interests of the Cooperative above personal reasons. During these negotiations, the Plaintiff was also not present to fulfill his obligations as a worker at the company even though he had received a warning letter. Thus, the Judge decided that the Plaintiff had no right to demand severance pay from the company. In order to accomplish its research goals, this study used a normative research methodology that relied on legislative approaches, a case approach, and the collection of both primary and secondary legal documents.Â